Towards lignin-derived chemicals using atom-efficient catalytic routes - Sudarsanam, Putla; Ruijten, Dieter; Liao, Yuhe; Renders, Tom; Koelewijn, Steven-Friso; Sels, Bert F. (Trends in Chemistry, 2020)
Lignin is a potential non-fossil resource of diverse functionalized phenolic units. The most important lignin- derived monomers are 4-alkylphenols, 4- hydroxybenzaldehydes, 4-hydroxybenzoic acids, and 4-hydroxycinnamic acids/esters. Efficient transformation of lignin and/or its monomers into valuable aromatics and their derivatives is crucial, not only for a sustainable lignocellulose biorefinery, but also to reduce our dependence on fossil feedstocks. This review provides a concise account of the recent advances in lignocellulose fractionation/lignin depolymerization processes towards lignin-derived monomers. Subsequently, numerous potential atom-efficient catalytic routes for upgrading lignin monomers into drop-in chemicals and new polymer building blocks are discussed.

Supported MoOx and WOx solid acids for biomass valorization: interplay of coordination chemistry, acidity, and catalysis - Sudarsanam, Putla; Gupta, Navneet Kumar; Mallesham, Baithy; Singh, Nittan; Kalbande, Pavan Narayan; Reddy, Benjaram M.; Sels, Bert F. (ACS Catalysis, 2021)
Supported molybdenum oxide (MoOx) and tungsten oxide (WOx) materials are a vital class of solid acid catalysts for the chemical industry because of their nontoxic nature, strong acidity, remarkable stability in water, hydrogen, and oxygen atmospheres, and excellent reusability performance. These fascinating solid acids play a pivotal role in developing sustainable catalytic routes for renewable biomass processing to produce value-added fuels, chemicals, and platform molecules. The coordination chemistry of MoOx and WOx on the support materials (oxides, carbons, or zeolites) controls their acidic strength, active site accessibility, and catalytic activity. Hence, significant efforts have been made toward optimizing the conditions used for catalyst synthesis and biomass processing to tune the coordination chemistry of MoOx and WOx with the substrate molecules and, thus, their acid-activity/selectivity performance. This Review provides a comprehensive overview of supported MoOx and WOx solid acids for biomass valorization. The importance of the biomass and the role of solid acids for biomass valorization were emphasized, followed by a brief discussion of supported MoOx and WO(x )solid acids. Afterward, the interplay of coordination chemistry, acidic strength, and catalytic activity of supported MoOx and WOx solid acids was discussed. Finally, their catalytic applications for the valorization of several biomass substrates and their derivatives were summarized. This Review will provide valuable insights for developing advanced supported WOx and MoOx solid acids for catalytic biomass valorization and other challenging acid-catalyzed processes.
Keywords: Acidity; biomass valorization; catalysis; Coordination chemistry; molybdenum oxide; tungsten oxide